KULTUR IN-VITRO EKSPLAN RIMPANG Zingiber zerumbet van aromaticum Val - Djadja Siti Hazar Hoesen (Research Center for Biology-Indonesian Institute of Sciences, 2004)
Zingiberaceae species Zingiber zerumbet var. aromaticum Val. usually propagated by vegetative part of the plant. Study on the proliferation of rhizome explants through in-vitro method were conducted on this species for propagation.The explants were cultured in MS (Murashige & Skoog) composition medium in normal and half strength concentration of macro elements, supplemented with micro elements and vitamins. Plant growth regulator (PGR) cytokinin (kinetin, adenine sulphate) were added in initiation stage.Benzyl adenine (BA), thidiazuron and 2,4D (dichlorophenoxy acetic acid) added in medium as treatments to induce shoot multiplication and adventitious shoot development or rooting plants.The media for induced multiple shoot and roots (plantlets) development, supplemented with PGR BA, thidiazuron, Indole butyric acid (D3A) as treatments and activated charcoal were added as antioxidant.In general, most of cultures were indicated have positively responds to PGR treatments. The ability of culture to produce multiple shoots and roots such as in medium with BAP (8 mg/1) + thidiazuron (0.1 mg/1) + IBA (1 mg/l)-indole butyric acid would give a better opportunity of rhizome explants proliferation and plantlets development of Z. zerumbet var. aromaticum.